Global vitamin D status problems: causes, pathogenetic mechanisms, treatment, prevention measures - N. A. Buralkina; E. E. Arutyunova; G. A. Vlasova (Медицинский совет, 2018)
There is a need to improve the status of vitamin D. Vitamin D not only affects the processes of formation of the musculoskeletal system, but also actively participates in many extra-osseous effects of cholecalciferol. Modern publications point to a number of positive effects of vitamin D for people of all ages. The modern vitamin D3 preparation Detrimax is recommended as an active food additive (tablet form containing 1000 IU of vitamin D3 (cholecalciferol)) and corresponds to the most frequent daily requirement for vitamin D3. Prophylaxis of vitamin D deficiency should be a priority in health policy.